Sanitary quality of seed of Paspalum species - da Silva, Stella Áurea Cristiane Gomes; dos Santos, Andreza Gonçalves; Loges, Vivian; de Castro, Ana Cecília Ribeiro; da Rosa, Regina Ceres Torres (Ornamental Horticulture, 2020)
Brazil has been developing research for selection of native species of Paspalum for use as turfgrass, nevertheless little is known about the sanitary quality and pathogens associated to the seeds, being the aims of this study. Subsamples of 100 seeds of two accessions of Paspalum notatum Flügge (PN 01 and PN 04) and one accesses of Paspalum lepton Schult. (PL 01) were submitted to the blotter test at 20 °C with a 12-h photoperiod for 7 days. The Penicillium and Curvularia genus incidence were highest in the three accessions of Paspalum. The seed health quality was variable between accessions, with more than 56% of incidence of the fungus Curvularia on the seeds. This study reported for the first time the occurrence of Curvularia spp. and Cladosporium herbarium in seeds of P. lepton, in the Northeast region of Brazil.